Early Clinical Expressions of Insulin Resistance: The Real Enemy to Look For - Rodríguez Gutiérrez, René; Salcido Montenegro, Alejandro; González González, José Gerardo (2018)
ABSTRACT The type 2 diabetes mellitus epidemic threatens public healthcare systems worldwide. Efforts to prevent chronic complications of diabetes and reduce their associated mortality have been ineffective. Hence, early prevention of type 2 diabetes mellitus and cardiovascular disease needs to be prioritized. This strategy, however, must be centered not on an approach based on hyperglycemia but on early pathophysiologic mechanisms, such as insulin resistance. Nonalcoholic fatty liver disease, androgenic alopecia, acanthosis nigricans, and polycystic ovarian syndrome are all well-accepted early clinical manifestations of insulin resistance that represent, in themselves, a risk for further development of type 2 diabetes and that appear years before hyperglycemia. Therefore, focusing efforts on detecting and rigorously treating patients with early clinical expression of insulin resistance (insulin resistance clinical syndrome) is probably the course of action that needs to be taken to counterbalance the type 2 diabetes mellitus epidemic.